Poetry and citizenship: notes on slam poetry in São Paulo and Rio de Janeiro from 2016-2020 - Silva de Freitas, Daniela (Brasiliana: Journal for Brazilian Studies, 2021)
The dispute towards the meanings of citizenship and poetry is one of the main concerns of the slam poetry produced in São Paulo and Rio de Janeiro between 2016 and 2020. This text analyzes works by Carol Dall Farra, Lucas Afonso, Luiza Romão, Luz Ribeiro, Mel Duarte, Roberta Estrela D’Alva, Tom Grito and Valentine and the context of their performance. It tries to foreground the mutually constitutive relationship between poetry and citizenship in the slam produced in these cities during this period. This relationship is grounded both at the level of the word, in the topics brought to discussion by the poets, and at the level of performance, in the enactment and collective pratice of slam poetry by the members of its community, its organizers, poets and audience members.